The haemagglutinin of Avibacterium paragallinarum is a trimeric autotransporter adhesin that confers haemagglutination, cell adherence and biofilm formation activities - Wang, Yi-Ping; Hsieh, Ming-Kun; Tan, Duen-Huey; Shien, Jui-Hung; Ou, Shan-Chia; Chen, Chih-Feng; Chang, Poa-Chun (Veterinary microbiology, 2014)
•HMTp210 is the major haemagglutinin of Av. paragallinarum.•HMTp210 is a trimeric autotransporter adhesin.•HMTp210 is involved in cell adherence and biofilms formation of Av. paragallinarum.•Targetron gene knockout system can be used in Av. paragallinarum. The haemagglutinin (HA) protein plays a key role in the immunogenicity and pathogenicity of Avibacterium paragallinarum. A 210-kDa protein (HMTp210) was previously reported to be the HA of Av. paragallinarum, but the biological function of HMTp210 is not well defined. In this study, mutant strains that lacked HMTp210 were constructed using the TargeTron® gene knockout system. Haemagglutination and haemagglutination-inhibition (HI) assays showed that the HMTp210-deficient mutants exhibited no HA activity and failed to elicit HI antibodies in immunized chickens. Additionally, HMTp210-deficient mutants exhibited reduced ability to adhere to HeLa cells and to form biofilms on abiotic surfaces. Virulence assays showed that HMTp210-deficient mutants are less virulent than their isogenic wild-type strains. HMTp210 bears significant similarity to proteins of the trimeric autotransporter adhesin (TAA) family, and recombinant HMTp210 expressed in E. coli formed a trimeric structure. Taken together, these results indicated that HMTp210 is a trimeric autotransporter adhesin that confers haemagglutination, cell adherence and biofilm formation activities. These results should prove valuable to further elucidate the biological function of HA and the mechanism of pathogenicity of Av. paragallinarum.